Access to P-Stereogenic Phosphinates via N-Heterocyclic Carbene-Catalyzed Desymmetrization of Bisphenols - Huang, Zhijian (2017)
A carbene-catalyzed desymmetrization of prochiral bisphenol compounds bearing remote P-stereogenic centers is disclosed. The catalytic reactions can be performed on gram scales with 1 mol % N-heterocyclic carbene (NHC) catalyst, providing efficient access to enantiomerically enriched P-stereogenic phosphinates. The chiral phosphinates prepared with our method can find widespread applications as asymmetric organic catalysts and ligands.